The Present Situation in the Philosophy of Science
X, 325 p.
Keywords: This volume is a serious attempt to open up the subject of European philosophy of science to real thought, and provide the structural basis for the interdisciplinary development of its specialist fields, but also to provoke reflection on the idea of ‘European philosophy of science’. This efforts should foster a contemporaneous reflection on what might be meant by philosophy of science in Europe and European philosophy of science, and how in fact awareness of it could assist philosophers interpret and motivate their research through a stronger collective identity. The overarching aim is to set the background for a collaborative project organising, systematising, and ultimately forging an identity for, European philosophy of science by creating research structures and developing research networks across Europe to promote its development. As such under the general rubric of ‘the present situation in the philosophy of science’, the emphasis is on as a first step identifying traditions andresearch structures already present, and the directions in which this research was leading. The European perspective in philosophy of science is the inclusion of the historical roots of current debates and the focus on methodological problems that cross the various sub-disciplines. This historical dimension is complemented by the evident broad scope of European philosophy of science which embodies not only a strong tradition of history and philosophy of science, history of philosophy of science, but also philosophy with respect to the cultural and social sciences as part of (not separate to) the discipline, combined with more traditional philosophical issues and approaches, such as the application of formal methods, the problem of realism, determinism and chance or the natural kinds debate. This consideration of general philosophical questions in science is married to a strong tradition of engaging naturalistically with the particular philosophical issues in individual sciences wherethere exists a prerogative of being closely schooled in the relevant scientific theory and research context. Additionally, one can refer to particular positions, like ‘structural realism’, as ‘European’, having their origin and their centre of pursuit, and indeed their historical links, in the context of European research.